1988
DOI: 10.1111/j.1600-0536.1988.tb02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and immediate‐type hypersensitivity to chlorhexidine

Abstract: A case with both contact urticaria and delayed-type contact allergy to chlorhexidine is presented. A review of the literature on hypersensitivity reactions of delayed and immediate type to this compound is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…The cutaneous application of chlorhexidine has been followed by anaphylactoid and immediate or delayed skin reactions of eczematous or urticarial type, but has never been implicated as a cause of bullous lesions. 5,6 Mupirocin is usually well tolerated, but can occasionally induce burn-type lesions, rash, edema, and exudation. 7 In 1987, Daly reported a case of vesicular dermatitis following the topical administration of mupirocin in a patient suffering from a chronic stasis dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cutaneous application of chlorhexidine has been followed by anaphylactoid and immediate or delayed skin reactions of eczematous or urticarial type, but has never been implicated as a cause of bullous lesions. 5,6 Mupirocin is usually well tolerated, but can occasionally induce burn-type lesions, rash, edema, and exudation. 7 In 1987, Daly reported a case of vesicular dermatitis following the topical administration of mupirocin in a patient suffering from a chronic stasis dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a delay of the implementation of contact isolation precautions for MRSA as recommended by the Centers for Disease Control and Prevention. 6 The mother had had prior contact with the healthcare system due to prenatal care. More detailed questioning after the result of the blood culture was known also revealed that she had been caring for an individual with a chronic wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an intact skin barrier cannot be assumed. Open application tests with chlorhexidine to undamaged skin in patients with immediate-type hyperreactivity have been reported in three of the reviewed articles [6,10,11]. Two showed a wheal after 1 h. The third was positive, but this might have been due to the mistaken application of chlorhexidine to a slightly exanthematous skin site [11].…”
Section: Discussionmentioning
confidence: 99%
“…29 Chlorhexidine has also been associated with potential anaphylactic reactions. [30][31][32] Studies with radiolabeled chlorhexidine mouthrinse have shown its ability to penetrate the intact mucosal barrier of the oral cavity or intestinal tract. 33,34 Ohtoshi et al 35 reported more than 30 cases of anaphylactic shock after the topical application of chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%